Bahamas. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in the Bahamas during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as good agricultural practices, research, trade, financing, market, fishing, school gardens, production, control of pests, technical support, food safety, through the Codex Alimentarius and value chains of ruminants, seeds, vegetables and tubers.